Comparative supercapacitance performance of CuO nanostructures for energy storage device applications1. Issue 26 (22nd March 2015) - Senthilkumar, V.; Kim, Yong Soo; Chandrasekaran, S.; Rajagopalan, Balasubramaniyan; Kim, Eui Jung; Chung, Jin Suk
<x xml:space="preserve">Abstract</x> (a)–(c) FE-SEM images of CuO nanoplates on Ni foam, flower-shaped CuO and bud-shaped CuO. (d) Specific capacitance and (d) and (e) Ragone plots of power density vs. energy density according to CuO electrodes in an asymmetrical device.